(untitled) (Revista ABRA, 2013)
Over the last years, the world has faced a process of major social reorganization, where spatial and geographical dimensions have been questioned. In this context, geography does not only refer to the material aspect of land, but to the other dimensions included. Consequently, this paper will study the progressive constitution of geography, the territory, and the place of the subject, for which it will be necessary to discuss the relationship between the body and the territory and the ways of subjectivation based on social and territorial relationships.